Retraction Note to: Redox modification of cysteine residues regulates the cytokine activity of high mobility group box-1 (HMGB1) - Huan Yang; Peter Lundbäck; Lars Ottosson; Helena Erlandsson-Harris; Emilie Venereau; Marco E. Bianchi; Yousef Al-Abed; Ulf Andersson; Kevin J. Tracey; Daniel J. Antoine (BMC, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s10020-020-00264-1